Ambient fine particulate matter exposure perturbed circadian rhythm and oscillations of lipid metabolism in adipose tissues. (July 2020) - Wang, Yixuan; Li, Ran; Chen, Rucheng; Gu, Weijia; Zhang, Lu; Gu, Jinge; Wang, Ziyao; Liu, Ying; Sun, Qinghua; Zhang, Kezhong; Liu, Cuiqing
Abstract: Emerging evidence indicated that disruption of circadian rhythm (CR) induced metabolic disorders, including dysregulation of energy homeostasis and lipid dysfunction, which was associated with ambient fine particulate matter (PM2.5 ) as well. However, the role and mechanism of CR in PM2.5 -mediated metabolic disorder remain unknown. In the present study, we investigated circadian rhythmic characteristics and explored the effect of PM2.5 on oscillating clock of lipid function and metabolism in white adipose tissue (WAT) and brown adipose tissue (BAT). C57BL/6 mice were exposed to PM2.5 in a whole-body inhalational exposure system. After 10 weeks, the expression of clock-related genes exhibits more robust CR in BAT than WAT, with the acrophase of PER2 in both types of adipose tissue being significantly decreased at ZT12 and Bmal1 increased at ZT0/24 in WAT in response to PM2.5 exposure. In addition, both CR pattern and expression levels of Sirt1 got significantly inhibited by PM2.5 exposure in WAT, accompanied with adipose dysfunction evidenced by inhibited pattern and expression levels of adipokines at the same ZT time points. Finally, a similar phase right shift from ZT4 to ZT12 in both Sirt3 and Ucp1 in BAT was induced by PM2.5 exposure. These findings indicate that disruption of the CR in adipose tissues could be an important way by which PM2.5 exposure induces metabolic disorder and provide potential targets for further investigation. Graphical abstract: Image 1 Highlights: Circadian rhythm of clock-related genes in both WAT and BAT was disrupted by PM2.5 exposure. Circadian rhythm of adipose genes in WAT was disrupted, which may be due to Sirt1 disturbance. Phase of Ucp1 in BAT was shifted to right, which may be due to Sirt3 disturbance.